Employee Compensation in Entrepreneurial Companies - Ola Bengtsson; John R. M. Hand (Research Institute of Industrial Economics (IFN), 2012)
Despite the central role played by human capital in entrepreneurship, little is known about how employees in entrepreneurial firms are compensated and incentivized. We address this gap in the literature by studying 18,935 non-CEO compensation contracts across 1,809 privately-held venture-backed companies. Our key finding is that employee compensation varies with the degree to which VCs versus founders control the business. We show that relative to founder-controlled firms, VC-controlled firms pay their hired-on (i.e., non-founder) employees higher cash salaries, provide stronger cash and equity incentives, and have more formal pay policies in place. We also observe that founder employees earn less cash pay and face weaker cash incentives than do hired-on employees, but have stronger equity incentives. We propose that the compensation differences we identify arise because the preferences and capabilities of controlling shareholders significantly influence the quality of the human capital attracted and retained by the firm.
Keywords: G24; J31; L26; 330; Venture capital; Entrepreneurship; Compensation contracts